Transtorno de déficit de atenção e hiperatividade em crianças portadoras de epilepsia - Karina Soares Loutfi (2010)
Introduction: Epileptic children have a high incidence of neuropsychiatric comorbidities, especially attention deficit hyperactivity disorder (ADHD), mood disorder and anxiety. Althout prevalent, the association between epilepsy and behaviour disorders are poorly understood. Methods: The study model was observational cross-sectional with 30 children with idiopathic epilepsy (30% generalized and 70% partial). We aimed to investigate symptoms consistent with ADHD DSM-IV diagnostic criteria. Patients underwent to neuropediatric evaluation and neuropsychological assessment. We applied the Brazilian versions of the Child Behaviour Checklist (CBCL), the Teacher Report Form (TRF) and the MTA-SNAP-IV questionnaire. For neuropsychological assessment we used The Wechsler Intelligence Scale for Children- Third edition (WISC-III) and a computerized test of visual attention (TAVIS-III). We evaluated the concordance between these behavioral scales and ADHD medical diagnosis. We sought to determine whether the presence of ADHD was correlated with variables closely linked to epilepsy or if there was correlation between the presence of ADHD with impairments on cognitive tests and in the performance on visual attentional computadorized tests. Results: ADHD diagnosis was established in 53.3% of children. The combined subtype was the most prevalent (43,7%), followed by the Hyperactive-impulsive (37,5%) and the inattentive subtype (18,7%). In ADHD patients, high scores in CBCL scales for other psychiatric comorbidities were frequent, specially for affective disorders (81,2%). There was a high concordance between ADHD diagnosis established by medical interview and scores above the cutoff point on the scales applied. In neuropsychological assessment were found evidences of cognitive impairments in a substantial proportion of patients: intellectually deficient scores were found in 17% of cases for total QI and 20% for verbal and executive QI. Poor performance on attentional tests was also identified. However, there was no statistical significance between the occurrence of ADHD and it´s subtypes and performance in the TAVIS-III, especially when we excluded intellectually deficient children. Regarding the variables related to epilepsy and the presence of ADHD, we found a correlation with statistical significance only in relation of age of onset and type of seizure, with higher prevalence of ADHD among children with the age of onset between 1 and 5 years when compared with children whose onset of seizures occurred after this age and greater chance of ADHD in children with partial seizures than in those with generalized seizures. As for the WISC-III, generalized epileptiform activity was associated with total QI compromised scores, as results of impaired perceptual organization index was associated with the presence of ADHD. Conclusions: Although the diagnosis of ADHD is based on DSM-IV criteria, the high prevalence of ADHD in association with other psychiatric comorbidities in epileptic children warrants the use of behavioral rating scales as a screening test. Neuropsychological assessment helps to identify strengths and difficulties of epileptic children, especiallly when there are behavioral complaints and signs of cognitive impairment.